2019
DOI: 10.1002/cbic.201900229
|View full text |Cite
|
Sign up to set email alerts
|

TiO2‐Based Photocatalysis at the Interface with Biology and Biomedicine

Abstract: The conversion of sunlight into chemical energy by using photosynthetic machinery is at the heart of nature and life. Scientists have also learned to use light energy to promote a great variety of chemical reactions, most of which are based on redox processes involving electron‐transfer steps. Indeed, the area of photoredox catalysis has recently emerged as one of the hottest fields in synthetic chemistry. Many of the photoredox reactions discovered so far take place in homogeneous phases, and rely on the use … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 237 publications
(143 reference statements)
0
11
0
Order By: Relevance
“…Titania has been widely applied in biomedicine owing to its chemical stability, biocompatibility, low cost, and adjustable properties. , Oxygen-deficient titania (TiO 2– x ), derived from titania and characterized with broadband optical absorbance from the near-infrared (NIR) to the ultraviolet, has acquired greatly extended application potential in biomedicine lately. , Recently, in advanced water treatment fields, TiO 2– x was used as a Fenton-like agent with a wider pH working window (pH = 2–9) compared to the traditional Fenton catalysts . Furthermore, the presence of more oxygen vacancy (OV) on TiO 2– x could efficiently strengthen its Fenton-like catalytic performance and dye adsorption capacity .…”
Section: Introductionmentioning
confidence: 99%
“…Titania has been widely applied in biomedicine owing to its chemical stability, biocompatibility, low cost, and adjustable properties. , Oxygen-deficient titania (TiO 2– x ), derived from titania and characterized with broadband optical absorbance from the near-infrared (NIR) to the ultraviolet, has acquired greatly extended application potential in biomedicine lately. , Recently, in advanced water treatment fields, TiO 2– x was used as a Fenton-like agent with a wider pH working window (pH = 2–9) compared to the traditional Fenton catalysts . Furthermore, the presence of more oxygen vacancy (OV) on TiO 2– x could efficiently strengthen its Fenton-like catalytic performance and dye adsorption capacity .…”
Section: Introductionmentioning
confidence: 99%
“…Other than applications in photocatalysts, TiO 2 -based modified nanomaterials have been widely applied in several areas including semiconductors, biology and medical research, energy storage and so on, as well. 25 Tomás-Gamasa et al 28 reported recent advances in TiO 2 used in biological fields. In this review, photodynamic therapy is concluded to be a promising strategy which needs further investigation.…”
Section: Wei Wangmentioning
confidence: 99%
“…Heterogeneous photocatalysis (HPC) is a photoactivated chemical reaction that became popular after Fujishima and Honda discovered the UV-driven photoelectrochemical water splitting reaction with a TiO 2 -based photoanode in 1972 (Figure 1). The effectiveness of HPC has been studied in many diverse fields, including environmental remediation [1,2], energy production [1], chemical engineering [3], medicine/biochemistry [4,5], agriculture [6], and multidisciplinary research areas [7] (Figure 1).…”
Section: Introductionmentioning
confidence: 99%